McDonald’s –the missing piece of restaurant business in Nigeria - Kravchenko, Tetiana; Ayesa, Oluwatosin Adeoluwa; Кравченко, Т.І.; Аєса, О.А. (Університет «КРОК», 2022)
The state of the quick service restaurants in Nigeria is very poor and this has led to an increasing need for an efficient and effective start-up in the main cities of Nigeria. For customers of fast-food restaurants, the motivation for consumer purchase is quick service, taste, diversity of dishes, healthy food, and convenience. This is very rare in Nigeria and investors can turn this problem into an opportunity for investment income through Franchising. As more Nigerians get involved with very challenging and demanding jobs, their eating pattern is significantly affected. From eating three meals in a day, these individuals now eat twice a day. The purpose of this article is to navigate through the minds of the Nigerian restaurant customers, identify potential customers, analyze and understand competitors’ business models while identifying Franchising as a point of entry. For investors to understand customer behavior and purchasing habit in Nigeria regarding restaurants, a survey was conducted on Consumer Preference on Fast-Food representatives of the Nigerian population with a focus on persons living in the popular urban areas of Nigeria which was generalized to represent the whole population. The perception of fastfood by respondents is that it is a quick fix service and a food option which some respondents do not consider unhealthy even if they do not encourage over-dependence on it. This is contrary to most findings and perceptions in studies in European and Asian countries hence offering a different dynamic to consumer behavior in Nigeria. The criteria for the analysis are Demographics, Behavioral, Purchase motivation, and Purchasing capacity. This brings about the means to figure out the wishes of customers and the value proposition that would be required by investors to achieve customer satisfaction. In this manner, the McDonald’s organization can create unswerving clients in Nigeria.

Стан ресторанів швидкого обслуговування в Нігерії дуже поганий, і це призвело до зростання потреби в ефективному запуску цього стартапу в головних містах Нігерії. Для клієнтів закладів швидкого харчування мотивацією купівлі є швидке обслуговування, смак, різноманітність страв, здорове харчування та зручність. Це дуже рідко можна зустріти у Нігерії, і інвестори можуть перетворити цю проблему на можливість отримати інвестиційний прибуток через франчайзинг. Оскільки все більше нігерійців займаються дуже складною та вимогливою роботою, це значно впливає на їх режим харчування. Замість трьох прийомів їжі на день ці люди їдять двічі на день. Метою цієї статті є визначення свідомості клієнтів нігерійських ресторанів, потенційних клієнтів, аналіз і розуміння бізнес-моделей конкурентів, а також визначення франчайзингу як точки входу. Для розуміння поведінки клієнтів ресторанів та їх купівельних звичок в Нігерії було проведено опитування окремих представників нігерійського населення щодо переваг фаст-фуду з акцентом на людей, які живуть у популярних міських районах Нігерії, яке після було узагальнено для представлення всього населення. Сприйняття фаст-фуду респондентами полягає в тому, що це сервіс швидкого вживання їжі, який деякі з них не вважають шкідливим для здоров’я, навіть якщо вони не відчувають надмірну залежність від нього. Це суперечить більшості висновків досліджень у європейських та азіатських країнах, отже, пропонує різнудинаміку поведінки споживачів у Нігерії. Критеріями для аналізу є демографічні показники, поведінка, мотивація купівлі та купівельна здатність. Це створює засоби для визначення побажань клієнтів і ціннісних пропозицій, які знадобляться інвесторам для досягнення задоволеності клієнтів. Таким чином, організація McDonald’s у Нігерії може створити постійних клієнтів у Нігерії.
Keywords: McDonald’s; Fast-Food Restaurant Business; Market Positioning; Competitors; Target Customers.; бізнес ресторанів швидкого харчування; позиціонування на ринку; конкуренти; цільові клієнти